THE EFFECT OF GUIDING QUESTIONS TECHNIQUE IN TEACHING STUDENTS TO WRITE CONTENT OF RECOUNT TEXT AT SMP NEGERI 1 SUNGGUMINASA - Nurhikmah Ismail; Nurdevi Bte Abdul; Andi Asri Jumiaty (English Language Teaching Methodology, 2022)
The objective of this research was to find whether there is significant effect of using Guiding Questions Technique in teaching students to write content of recount text at SMP Negeri 1 Sungguminasa. The method of this research was pre-experimental with one group pre-test and post-test design. The data gathered from pre-test, treatment, and post-test. The result of this research revealed that there was significant effect from students' writings after they applied Guiding Questions Technique to write content of recount text. It was proved from the results of pre-test mean score (48.33) and the post-test mean score was (81.67). Besides, the t-test value (15.418) was higher than the t-table value (1.6991). Based on the data results, it was concluded that Guiding Questions Technique brought significant effect while teaching students to write content of recount text.